2006
DOI: 10.1080/17439760600566008
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of personal meaning systems: A new approach to measuring meaning of life

Abstract: This article introduces a new qualitative-quantitative approach to assess meaning of life. The participants described their sources of meaning and how they were interconnected. Four quantitative measures for (1) the accessibility of meaningrelated knowledge, the degree of (2) differentiation and (3) elaboration of personal meaning systems, and (4) their coherence were calculated. The sample consisted of 59 theology and science students. The study tested (a) whether the structural properties of personal meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 18 publications
3
42
0
Order By: Relevance
“…Research has found that a strong commitment to (i.e., intense endorsement of) one's sources of meaning in life is advantageous for wellbeing (Battista & Almond, 1973;Pöhlmann et al, 2006). Consistent with this hypothesis, the present research found that those adults who highly endorsed meaning from work, family, interpersonal relationships, community/society issues, and life in general experienced greater overall meaning in life and greater wellbeing, and that highly endorsing meaning from religiosity/spirituality meant greater presence.…”
Section: Moderate Domains Highly Endorsedsupporting
confidence: 78%
See 2 more Smart Citations
“…Research has found that a strong commitment to (i.e., intense endorsement of) one's sources of meaning in life is advantageous for wellbeing (Battista & Almond, 1973;Pöhlmann et al, 2006). Consistent with this hypothesis, the present research found that those adults who highly endorsed meaning from work, family, interpersonal relationships, community/society issues, and life in general experienced greater overall meaning in life and greater wellbeing, and that highly endorsing meaning from religiosity/spirituality meant greater presence.…”
Section: Moderate Domains Highly Endorsedsupporting
confidence: 78%
“…Being intensely and strongly committed to one's meaning in life has been found to be beneficial for wellbeing (Battista & Almond, 1973;Pöhlmann et al, 2006). Extrapolating from this finding, we hypothesise that strongly endorsing sources of meaning results in higher wellbeing and presence of meaning, but results in diminished search for meaning (Hypothesis 3).…”
Section: Goals Of the Present Studymentioning
confidence: 81%
See 1 more Smart Citation
“…Other aspects of global meaning have received less attention, such as the structural characteristics of core beliefs and goals (e.g. degree of differentiation, elaboration, or conflict among these elements) (Emmons, Colby, & Kaiser, 1998;Pohlmann, Gruss, & Joraschky, 2006;Park, 2010). The manner in which global meaning may be violated by serious illness is another area in need of further investigation (Park & Folkman, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…To find personal meaning is to understand the nature of one's life, and to feel that life is significant, important, worthwhile, or purposeful (Frankl, 1963(Frankl, , 1978. In Frankl's theory, meaning is a broad construct that is conceptually and empirically related to many domains; positive associations of meaning are found in relation to constructs such as hope, faith, subjective well-being, and happiness, as well as negative associations between meaning and depression, anxiety, psychological distress, boredom proneness, and drug/alcohol use (Melton & Schulenberg, 2007Pöhlmann, Gruss, & Joraschky, 2006;Schulenberg et al, 2008). Frankl's theory of meaning has been used as a basis for research and practice in many fields, including medicine, psychology, counseling, education, ministry, and nursing (Starck, 2008).…”
mentioning
confidence: 97%